PROVEN CRIMINAL ACTION OF SPREADING HOAX NEWS THROUGH SOCIAL MEDIA REGARDING COVID-19 - krismiyarsi krismiyarsi (UNTAG Law Review, 2021)
The spread of Corona Virus Disease 2019 (COVID-19) in Indonesia, is used by irresponsible people to spread fake news (hoaxes) that can disturb the public. The ITE Law in it has regulated the crime of hoaxes, the perpetrators can be subject to criminal sanctions, however, the sanctions in the ITE Law do not prevent people from spreading false news through social media, many cases occur in the community regarding these crimes, but problems arise in proving the hoax crime case, where it is not the ITE Law that is used as the basis for convicting the perpetrator but using Article 14 of Law no. 1 of 1946, namely spreading false news conventionally without any element of electronic means, this is because the Criminal Procedure Code does not regulate digital evidence.